Analysis Implementation of the Habituation Method in Learning to Memorize the Al-Qur’an at SDN 1 Sawangan - Listiana, Listiana; Tri A, Sarah; K. W, Anisa; N, Faidatun; L. M. S, Intan; A, Zahidatul; Fatimah, Siti (Proceeding International Conference on Religion, Science and Education, 2025)
The habituation method is a path that is taken to memorize the holy verses of the Al-Qur’an so that they continue to enter and be maintained in the heart and mind. Routine activities carried out before each lesson in the process of memorizing the Al-Qur’an are carried out at SDN 1 Sawangan. The research model adopted is Qualitative Descriptive. The subject of this research is the PAI Teacher at SDN 1 Sawangan. The research instruments used in this research were observation, interviews, and documentation. From the results of the data obtained, it was found that the habituation method to increase the achievement of SDN 1 Sawangan students in memorizing the Al-Qur’an was considered good and continued to experience an increase in Al-Qur’an memorization every semester, this was due to the habituation method carried out to cultivate culture. memorize continuously (istiqomah) in accordance with the expected goals. This is quite effective and has a positive impact on students because it can form a culture of always memorizing the Al-Qur’an and making it difficult to leave it behind. Meanwhile, minority students still experience problems in memorizing, this is caused by different individual ability backgrounds.